Effect of combined Ce and Er Addition on Solidification, Microstructure of the Al-7Si-alloy - Majeed, Faraj Saeid Adrees; Suhaimi, Mohd Azlan; Mohd Yusof, Nordin; Nabgan, Walid; Ahmad, Rosli; Asmael, Mohammed Basher; Hj.Yusof, Mohd Sallehuddin; Abdullah, Suhail Najm (UTHM Publishing, 2020)
This paper highlights the effects of the additions of two rare earth elements (REEs) (Ce and Er) on microstructure and to investigate the characteristic temperatures during solidification of the modified alloy. Five changes of Al-7Si alloys with xEr+xCe additions (x=0.15, 0.25, 0.4, 0.5 and 0.75) were produced by casting technique via the solidification parameters examined using computer-aided cooling curve thermal analysis (CA-CCTA). The thermal analysis tests were carried out for each one by using a thermal analysis system that includes (K-type Thermocouple, EPAD-TH8-K, EPAD-Baes2 and Laptop with Dewesoft-7.5-Lt). To estimate the change in microstructure and solidification as a result of adding (Ce+Er) additions, the obtained result showed that the growth TG Al-Phase and nucleation TN Al-Phase temperatures decreased to lower temperatures 614.7°C and 615.5°C respectively as the amount Ce, Er increased.